The impact of unit delimitation on exegesis - Hoop, Raymond de.; Korpel, Marjo C. A. 1958-; Porter, Stanley E., 1956- (Pericope, 2009)
This volume contains papers dealing with the impact of unit delimitation on exegesis. Pargraph markers play an important role in literature, this is illustrated by means of the examples of Mark 12:13-27 and Romans 1:21-25. The setumah after Isaiah 8:16 is significant for understanding the making of the Hebrew Bible. Furthermore, it is demonstrated that the text divisions in the Book of Daniel guide the reading of the text. The demarcation of hymns and prayers in the prophets is illustrated by the examples of Hosea 6:1-3 and Isaiah 42:10-12. Unit delimitation is taken up for the theory of an acrostichon in Nahum 1. Also discussed is the delimitation of units in Genesis, Isaiah 56:1-9, and Jeremiah and Habakkuk.